Formulaic or Felt? Investigating the Use of “How’s your day?” in an International Primary Classroom - Maryam, Sitti (Lexeme : Journal of Linguistics and Applied Linguistics, 2026)
This study investigates the pragmatic and cultural function of the phrase “How’s your day?” in an international primary school classroom in Makassar, Indonesia. Drawing from reflective observation and daily interaction with Grade 4 to 6 students, the research explores how this simple conversational question facilitates students’ confidence, expressiveness, and natural use of English. The study adopts a reflective descriptive design, built on long-term classroom experiences, observation and interaction with students -where English served as the primary language of communication. The data were generated through memory-based reconstruction, reflective journals, and non-recorded classroom observations. The analysis followed a thematic reflection approach.  Findings reveal that “How’s your day?” operates as more than a casual greeting. It acts as a social bridge fostering authentic communication, empathy, and a sense of belonging among young learners. Students initially responded formulaically but gradually developed ownership of the phrase, using it spontaneously with peers, teachers, and even family members. The exchange nurtured natural speech habits and pragmatic awareness, showing that emotional engagement and context-rich interactions enhance language learning more effectively than rigid grammar-based instruction. Pedagogically, the study highlights the importance of integrating authentic conversational routines into English language teaching, especially in multilingual environments. Such interactions humanize communication, promote cultural understanding, and support affective dimensions of language learning. The study concludes that teaching English expressiveness is not only about fluency but also about connection, confidence, and care values embedded in meaningful conversation